Protective effects of dapagliflozin on vascular remodeling in the carotid artery following balloon injury – potential role of angiotensin and purinergic signaling. (14th October 2021) - Matsushita, K; Sato, C; Bruckert, C; Gong, D; Hmadeh, S; Fakih, W; Remila, L; Auger, C; Jesel, L; Ohlmann, P; Kauffenstein, G; Schini-Kerth, V; et al.
Abstract: Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have been shown to reduce the risk of cardiovascular events independently of glycemic control. The possibility that SGLT2 inhibitors improve endothelial regeneration and vascular restenosis is unknown. Purpose: To examine whether dapagliflozin, a selective SGLT2 inhibitor, could prevent neointima thickening induced by balloon injury and, if so, to determine the underlying mechanisms. The effect of dapagliflozin was compared to that of losartan, an angiotensin type 1 receptor (AT1R) antagonist. Methods: Saline, dapagliflozin (1.5 mg/kg/day), or losartan (30 mg/kg/day) were administered orally for 5 weeks to male Wistar rats. Balloon injury of the left carotid artery was performed 1 week after starting the treatment and sacrificed 4 weeks later. Vascular reactivity was assessed on left (injured) and right (healthy) carotid artery rings. The extent of neointima was assessed by histomorphometric analysis, changes of target factors by immunofluorescence, RT-qPCR and histochemistry. Results: Dapagliflozin and losartan treatments reduced neointima thickening by 32% and 27%, respectively. Blunted contractile responses to phenylephrine and relaxations to acetylcholine and down-regulation of eNOS were observed in the injured artery. These effects were not modified by the dapagliflozin or the losartan treatments. RT-qPCR investigations indicated an increased in gene expression of inflammatory (IL-1beta, ITGAM, VCAM-1), oxidative (p47phox, p22phox) and fibrotic (TGF-beta1) markers and a decreased of eNOS in the injured carotid. However, these changes were not affected by the pharmacological treatments. By contrast, significant increased levels of AT1R angiotensin receptor and NTPDase1 (CD39) ectonucleotidase were observed in the restenotic carotid artery of the dapagliflozin group. Histochemical analysis evidenced important NTPDase1 activity in the neointima. Conclusions: Dapagliflozin effectively reduced neointimal thickening. As the contribution of AT1R and P2Y2 ATP receptor in smooth muscle cell proliferation and neointima formation has been reported in the literature, the present data suggest that dapagliflozin prevents restenosis through interfering with angiotensin and/or extracellular nucleotides signaling. SGLT2 transporter represent potential new target for limiting vascular restenosis. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This work was supported by AstraZeneca